Environmental impact of hybrid and electric vehicles - Wu,B; Offer,G (Royal Society of Chemistry, 2017)
Hybrid and electric vehicles play a critical role in reducing global greenhouse gas emissions, with transport estimated to contribute to 14% of the 49 GtCO2eq produced annually. Analysis of only the conversion efficiency of powertrain technologies can be misleading, with pure battery electric and hybrid vehicles reporting average efficiencies of 92% and 35% in comparison with 21% for internal combustion engine vehicles. A fairer comparison would be to consider the well-to-wheel efficiency, which reduces the numbers to 21–67%, 25% and 12%, respectively. The large variation in well-to-wheel efficiency of pure battery electric vehicles highlights the importance of renewable energy generation in order to achieve true environmental benefits. When calculating the energy return on investment of the various technologies based on the current energy generation mix, hybrid vehicles show the greatest environmental benefits, although this would change if electricity was made with high amounts of renewables. In an extreme scenario with heavy coal generation, the CO2eq return on investment can actually be negative for pure electric vehicles, highlighting the importance of renewable energy generation further. The energy impact of production is generally small (∼6% of lifetime energy) and, similarly, recycling is of a comparable magnitude, but it is less well studied.